Thrombolysis by PLAT/tPA increases serum free IGF1 leading to a decrease of deleterious autophagy following brain ischemia. Issue 6 (3rd June 2022) - Thiebaut, Audrey M.; Buendia, Izaskun; Ginet, Vanessa; Lemarchand, Eloise; Boudjadja, Mehdi Boutagouga; Hommet, Yannick; Lebouvier, Laurent; Lechevallier, Charlotte; Maillasson, Mike; Hedou, Elodie; Déglon, Nicole; Oury, Franck; et al.
ABSTRACT: Cerebral ischemia is a pathology involving a cascade of cellular mechanisms, leading to the deregulation of proteostasis, including macroautophagy/autophagy, and finally to neuronal death. If it is now accepted that cerebral ischemia induces autophagy, the effect of thrombolysis/energy recovery on proteostasis remains unknown. Here, we investigated the effect of thrombolysis by PLAT/tPA (plasminogen activator, tissue) on autophagy and neuronal death. In two in vitro models of hypoxia reperfusion and an in vivo model of thromboembolic stroke with thrombolysis by PLAT/tPA, we found that ischemia enhances neuronal deleterious autophagy. Interestingly, PLAT/tPA decreases autophagy to mediate neuroprotection by modulating the PI3K-AKT-MTOR pathways both in vitro and in vivo . We identified IGF1R (insulin-like growth factor I receptor; a tyrosine kinase receptor) as the effective receptor and showed in vitro, in vivo and in human stroke patients and that PLAT/tPA is able to degrade IGFBP3 (insulin-like growth factor binding protein 3) to increase IGF1 (insulin-like growth factor 1) bioavailability and thus IGF1R activation. Abbreviations: AKT/protein kinase B: thymoma viral proto-oncogene 1; EGFR: epidermal growth factor receptor; Hx: hypoxia; IGF1: insulin-like growth factor 1; IGF1R: insulin-like growth factor I receptor; IGFBP3: insulin-like growth factor binding protein 3; Ka: Kainate; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MAPK/ERK: mitogen-activated protein kinase; MTOR: mechanistic target of rapamycin kinase; MTORC1: MTOR complex 1; OGD: oxygen and glucose deprivation; OGDreox : oxygen and glucose deprivation + reoxygentation; PepA: pepstatin A1; PI3K: phosphoinositide 3-kinase; PLAT/tPA: plasminogen activator, tissue; PPP: picropodophyllin; SCH77: SCH772984; ULK1: unc-51 like kinase 1; Wort: wortmannin